Assessment of oral health status and related factors in adolescents aged 12-15 years in the Gansu Province of China: a cross-sectional survey - Zhidong Zhang; Di Wang; Jian Zhao; Dandan Wang; Baoping Zhang (BMC, 2023)
Abstract Background The national oral epidemiological survey conducted every decade has become an indispensable means of detecting changes in oral disease patterns. This study was undertaken to investigate the oral health status and related factors in 12-15-year-old students in Gansu, China. Methods According to the methodology adopted by the Fourth National Oral Health Survey, a multi-stage, stratified, random sampling method was used to select 3871 adolescents aged 12-15 years from four regions of Gansu Province for oral examination and questionnaire survey. Caries experience was measured using the Decayed, Missing, and Filled Teeth (DMFT) index; and periodontal health examination included gingival bleeding, calculus, periodontal pockets and attachment loss. The questionnaire included questions regarding sociodemographic characteristics, and oral health knowledge and behaviors. SPSS20.0 software was used for statistical analysis of the survey data. Results The mean DMFT index was 0.83 ± 1.42. The prevalence of caries experience was 38.6%, filling rate was 1.6%, and pit and fissure sealing rate was 0.5%. Logistic regression analysis showed that female sex, rural district, older age, non-only child, frequency of dental visits, and toothache experience were the risk factors for caries experience, with OR ranging between 1.280 and 3.831 (p < 0.05). Prevalence of healthy periodontium was 29.8%. Female sex, rural district, and younger age were found to be the protective factors for healthy periodontium, with OR ranging between 1.178 and 1.414 (p < 0.05). Conclusions Adolescents in Gansu Province had high prevalence of caries experience along with low filling rate, and low prevalence of healthy periodontium. Therefore, it is necessary to vigorously strengthen oral health education, disease prevention and control programs in the province. This would help improve the oral health-related quality of life of these individuals.